Epigeous macrofungi of the Parque de Natureza de Noudar in Alentejo (Portugal) - Louro, R.; Calado, M.; Pinto, B.; Santos-Silva, C. (Mycotaxon, 2009)
This inventory represents the first list of the epigeous macrofungi collected in Parque de Natureza de Noudar (Barrancos, Alentejo, Portugal). Throughout 3 years 162 taxa were registered, from which 8 are new species for Portugal and 77 for Alentejo. Some of them are considered rare species whereas others have been suggested to acquire a conservation status.
Keywords: fungi; Holm oak; iberian peninsula; Mediterranean ecosystem; sporocarps